Ever constant [large type] - Peterson, Tracie; Woodhouse, Kimberley, 1973- (Peterson, Tracie. Treasures of Nome, 2022)
"She's always determined to be the stable, reliable one. But now her commitment may destroy her. On the surface, Whitney Powell is happy working with her sled dogs and welcoming the new additions to her family through her sisters' marriages and an upcoming birth. But her life is full of complications, including an estranged father, that have her on the edge of losing control. Growing up, she was the strong sister, and she can't give that up now.When villagers in outlying areas come down with a horrible sickness, Dr. Peter Cameron turns to Whitney and her dogs for help navigating the deep snow, and they become close while ministering to the sick together. Peter has long recognized her finer qualities but is troubled by the emotions and secrets she keeps buried within. He wants to help but wonders if she is more of a risk than his heart can take. As sickness spreads throughout Nome and another man courts Whitney, she and Peter will discover that sometimes it is only in weakness that you can find strength"--